Interaction of wave with multiple wide polynyas - Shi, YY; Li, ZF; Wu, GX (AMER INST PHYSICS, 2019)
A method based on the wide spacing approximation is applied to the wave scattering problem in multiple polynyas. An ice sheet is modeled as an elastic plate, and fluid flow is described by the velocity potential theory. The solution procedure is constructed based on the assumption that the ice sheet length is much larger than the wavelength. For each polynya, of free surface with an ice sheet on each side, the problem is solved exactly within the framework of the linearized velocity potential theory. This is then matched with the solution from neighboring polynyas at their interfaces below the ice sheet on each side, and only the traveling waves are included in the matching. Numerical results are provided to show that the method is very accurate and highly efficient. Extensive simulations are then carried out to investigate the effects of the ice sheet number, ice sheet length, distribution of ice sheets, as well as polynya width. The features of wave reflection and transmission are analyzed, and the physical mechanism is discussed.